Children of Migrants: The Impact of Parental Migration on Their Children's Education and Health Outcomes - Xin Meng; Chikako Yamauchi (Institute for the Study of Labor (IZA), 2015)
In the past 15 years around 160 million Chinese rural workers migrated to cities to work. Because of restrictions on migrant access to local health and education system a large cohort of migrant children are left-behind in rural villages and growing up without parental care. This paper examines how parental migration affects children's health and education outcomes. Using the Rural-Urban Migration Survey in China (RUMiC) data we are able to measure the share of children's lifetime during which parents migrated away from home. By instrumenting this measure of parental migration with weather changes in their home village when they were young we find a sizable adverse impact of exposure to parental migration on children's health and education outcomes. We also find that what the literature has always done (using contemporaneous measure for parental migration) is likely to underestimate the effect of exposure to parental migration on children's outcomes.
Keywords: J38; I28; 330; migration; children; education; health; China